Mandibular morphometry applied to local anaesthetic blockage in the capybara (Hydrochoerus hydrochaeris) - Oliveira, Elton Luís Ritir [UNESP] (2022)
Capybaras have been victims of collisions against vehicles, which can result in fractures of the teeth and mandible. Then, a local anaesthetic block of the inferior alveolar and mental nerves is important for performing therapeutic procedures in the oral cavity of these rodents. Thus, the aim of this study was to describe the mandibular morphometry of the capybara with emphasis on the establishment of anatomic references for anaesthetic block of the inferior alveolar and mental nerves. For this, mandibles from eight young and adult capybaras were used. Radiography and morphometry of the capybara hemimandible were performed. The mandibular foramen had a dorsoventral diameter of 2.1 mm in young and 2.2 mm in adult capybaras, and it was situated ventrally to the third molar tooth. For extraoral block of the inferior alveolar nerve, the needle should be introduced obliquely 63.5 and 77.4 mm from the angular process in young and adult capybaras, respectively. In another extraoral approach, the needle should be introduced perpendicularly 20.8 mm in young and 26.3 mm in adult animals from the ventral margin of the capybara mandible. For blocking only the mental nerve, the needle should be inserted perpendicularly from the interalveolar margin, 10.7 and 11.5 mm in the young and adult capybaras, respectively. The findings of this study suggest that the age group should be taken into account when performing the anaesthetic block of the inferior alveolar and mental nerves in capybaras.